Redefining the reference librarian in the university environment - Lenuța Ursachi (Revista Română de Biblioteconomie și Știința Informării, 2021)
The reference librarian and the services provided hold more than ever the attention of users at the “Dunărea de Jos” University Library of Galați (DJULG). The Internet, technology and struggle for survival left a significant mark on both librarians' skills and reference services in the new context of the information society. In order to align with new trends in librarianship and to respond effectively to the increasingly complex demands of users, the reference librarians had to move beyond the traditional and reinvent themselves. As a result, new skills have been acquired and new services emerged in the information landscape of the university library.